A pyridinium cation-containing polyquaternary ammonium anion exchange membrane and a preparation method thereof

CN122940963APending Publication Date: 2026-10-20SUZHOU IND PARK HESHUN ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611333100.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]目前,阴离子交换膜的性能提升面临两大核心瓶颈;其一,离子传导率与尺寸稳定性之间存在难以兼顾的瓶颈:提高离子交换容量(IEC)虽能提升电导率,但会导致膜过度吸水溶胀,机械强度下降;反之,低IEC虽能保证尺寸稳定性,但电导率无法满足应用需求

Benefits of technology

1.该含吡啶阳离子的多季铵阴离子交换膜及其制备方法,以无醚键聚芳基吡啶为骨架,从根本上避免了醚键在碱性条件下的降解风险,赋予膜材料优异的耐碱稳定性;同时通过Menshutkin反应在吡啶氮原子上接枝含一至三个季铵阳离子的柔性侧链,实现了对侧链阳离子数目的精确调控,多阳离子结构与长柔性侧链协同构建连续高效的离子传输通道,并借助阳离子间的静电排斥作用有效抑制聚合物链的过度伸展,从而在提升离子传导率的同时实现低溶胀率的良好平衡,使所得阴离子交换膜兼具高电导率、优良尺寸稳定性与耐碱性,可满足阴离子交换膜电解水制氢等场景的应用需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a multi-quaternary ammonium anion exchange membrane containing pyridine cations and its preparation method, relating to the field of ion exchange membrane materials technology. The anion exchange membrane uses ether-free polyarylpyridine as its backbone, which is formed by the superacid-catalyzed Friedel-Crafts hydroxyalkylation reaction of aromatic hydrocarbons and 4-acetylpyridine. Flexible side chains containing one to three quaternary ammonium cation groups are grafted onto the nitrogen atoms of the pyridine backbone via the Menshutkin reaction, forming repeating units as shown in the general structural formula. This invention fundamentally avoids the risk of ether bond degradation under alkaline conditions, endowing the membrane material with excellent alkali resistance and stability. Simultaneously, it achieves precise control over the number of side chain cations, achieving a good balance between improved ion conductivity and low swelling rate, resulting in anion exchange membranes that possess high conductivity, excellent dimensional stability, and alkali resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ion exchange membrane materials technology, specifically to a multi-quaternary ammonium anion exchange membrane containing pyridine cations and its preparation method. Background Technology

[0002] Hydrogen energy, with its high energy density and zero carbon emissions, is considered a crucial technology for addressing global energy challenges. Anion exchange membrane electrolysis (AEMWE) for hydrogen production has become a cutting-edge technology for green hydrogen production due to its ability to use non-precious metal catalysts, high gas purity, low-cost membrane materials, and rapid response to fluctuating energy levels.

[0003] The main function of anion exchange membranes (AEMs) is to transfer hydroxide ions, isolate the anode and cathode, and prevent the passage of gases at both electrodes. Therefore, they must meet the following requirements: high hydroxide ion conductivity to increase electrolysis current density; good mechanical strength and dimensional stability; excellent alkali chemical stability; and low production cost.

[0004] Currently, improving the performance of anion exchange membranes faces two major bottlenecks. First, there is a trade-off between ionic conductivity and dimensional stability: increasing the ion exchange capacity (IEC) can improve conductivity, but it can lead to excessive water absorption and swelling of the membrane, resulting in decreased mechanical strength; conversely, while a low IEC can ensure dimensional stability, the conductivity cannot meet application requirements. Second, there is insufficient long-term alkali resistance; existing ether-containing backbones are easily degraded by OH- nucleophilic attack in alkaline environments, while traditional quaternary ammonium cations are also easily decomposed through Hoffmann elimination or nucleophilic substitution pathways. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a multi-quaternary ammonium anion exchange membrane containing pyridine cations and its preparation method, thus solving the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides a multi-quaternary ammonium anion exchange membrane containing pyridine cations, comprising the following general structural formula: Where n is the degree of polymerization, Ar is the aromatic hydrocarbon residue, NR represents the flexible side chain R grafted onto the nitrogen atom of the pyridine ring, and OH - It is a para ion.

[0007] Furthermore, in the general formula, the R structure can be any of the following: Monoquaternary ammonium cationic side chain: —(CH2)6—N + (CH3)3; Biquaternary ammonium cationic side chain: —(CH2)4—N + (CH3)2—(CH2)6—N+ (CH3)3; The triquaternary ammonium cationic side chain is derived from the Br-DQA bisquaternary ammonium salt, the structure of which is [Br - [(CH3)3N] + —(CH2)6—N + [(CH3)2—(CH2)4—Br], with the ion being Br. - The general structural formula is as follows: .

[0008] Furthermore, in the general structural formula, the Ar structure can be any one of the following: a terphenyl residue or a biphenyl residue; the general structural formula is as follows: .

[0009] A method for preparing a multi-quaternary ammonium anion exchange membrane containing pyridine cations, for use in preparing the above-mentioned multi-quaternary ammonium anion exchange membrane containing pyridine cations, includes the following steps: S1. Synthesis of precursor polymer: Using aromatic hydrocarbons and 4-acetylpyridine as monomers, dichloromethane as solvent, and trifluoromethanesulfonic acid as catalyst, polyarylpyridine precursors are synthesized via superacid-catalyzed Friedel-Crafts hydroxyalkylation reaction. The molar ratio of the aromatic hydrocarbon to 4-acetylpyridine and trifluoromethanesulfonic acid is 1:1 to 2:5 to 10, the reaction temperature is 0°C to room temperature, and the reaction time is 12 to 24 hours. S2. Preparation of quaternized polymer: The precursor polymer obtained in step S2 is dissolved in a polar solvent, and an alkali and a quaternizing agent are added successively. The reaction is carried out at 60-80℃ for 48-120 hours. After precipitation, washing and drying, the quaternized polymer is obtained. The quaternizing agent is selected from iodomethane, 1-bromo-6-trimethylammonium hexyl bromide or Br-DQA bisquaternary ammonium salt, respectively, to prepare monocationic, dicationic and tricationic side chain polymers. S3. Preparation of anion exchange membrane: Dissolve the quaternized polymer obtained in step S2 in a polar solvent to prepare a homogeneous casting solution with a polymer mass fraction of 5-15 wt%. After filtration and degassing through a glass frit funnel (G2), the solution is uniformly cast onto a clean horizontal glass plate or flat plate to form a wet membrane. The thickness of the wet membrane is set by adjusting the gap between the doctor blade and the die lip. h_wet = h_dry × (1 + k / w) Where h_dry is the target dry film thickness of 30~80μm, w is the polymer mass fraction of the casting solution, and k is the solid content correction coefficient, with a value range of 0.85~1.15, which decreases with the increase of the number of quaternary ammonium cations in the flexible side chain. The glass plate with the film was then placed in a segmented temperature-controlled oven for three-stage controlled drying with film surface temperature feedback to obtain OH. - Anion exchange membrane in the form of anion exchange membrane.

[0010] Furthermore, in step S2, the Br-DQA bisquaternary ammonium salt is synthesized by a two-step method: first, iodomethane is reacted with N,N,N',N'-tetramethyl-1,6-hexanediamine to generate a monoquaternized intermediate, and then the intermediate is reacted with 1,4-dibromobutane to generate Br-DQA.

[0011] Furthermore, dimethyl sulfoxide is selected as the polar solvent; anhydrous potassium carbonate is selected as the base.

[0012] Furthermore, in step S3, the value of k is: k≈1.0 for a single quaternary ammonium side chain, k≈0.95 for a double quaternary ammonium side chain, and k≈0.90 for a triple quaternary ammonium side chain. Furthermore, in step S3, the three-stage controlled drying with film surface temperature feedback is specifically as follows: The first stage involves drying at a membrane surface temperature of 30-50℃ for 0.5-2 hours to establish a solvent evaporation gradient and induce the initial aggregation of side-chain cation clusters. The second stage involves drying the film surface at a temperature of 50-70℃ for 2-6 hours to reduce the solvent residue to below 2wt% and allow the cationic clusters of the multi-quaternary ammonium flexible side chains to aggregate in an orderly manner within the reversible swelling window near the polymer's glass transition temperature Tg, forming a continuous ion conduction channel. The third stage involves drying at a film surface temperature of 70~90℃ and not exceeding 110℃ for 0.5~2 hours to eliminate residual stress and reduce solvent residue to below 0.5wt%. The oven hot air temperature is dynamically adjusted based on the real-time monitoring of the film surface temperature by a non-contact temperature sensor closely attached to the film surface. The film surface temperature does not exceed 110℃ throughout the drying process to protect the quaternary ammonium cation groups from degradation due to high temperatures. The quaternized polymer has an ether-free polyarylpyridine backbone, and flexible side chains containing 1-3 quaternary ammonium cation groups are grafted onto its pyridine nitrogen atoms. The resulting film is immersed in a 1 M KOH or NaOH solution and subjected to alkali exchange at 60-80℃ for 12-24 hours to obtain OH... - Anion exchange membrane in the form of anion exchange membrane.

[0013] This invention provides a multi-quaternary ammonium anion exchange membrane containing pyridine cations and its preparation method, which has the following beneficial effects: 1. This multi-quaternary ammonium anion exchange membrane containing pyridine cations and its preparation method utilize ether-free polyarylpyridine as the backbone, fundamentally avoiding the risk of ether degradation under alkaline conditions and endowing the membrane material with excellent alkali resistance. Simultaneously, flexible side chains containing one to three quaternary ammonium cations are grafted onto the pyridine nitrogen atom via the Menshutkin reaction, achieving precise control over the number of side chain cations. The multi-cation structure and long flexible side chains synergistically construct a continuous and efficient ion transport channel, and the electrostatic repulsion between cations effectively inhibits excessive extension of the polymer chain. This achieves a good balance between improved ion conductivity and low swelling rate, resulting in anion exchange membranes that possess high conductivity, excellent dimensional stability, and alkali resistance, meeting the application requirements of anion exchange membranes in water electrolysis for hydrogen production.

[0014] 2. The multi-quaternary ammonium anion exchange membrane containing pyridine cations and its preparation method introduce a three-stage controlled drying process in the film-forming and drying steps, which involves Tg-anchor critical thickness control and membrane surface temperature feedback: By using the glass transition temperature as an anchor point and combining a solid content correction coefficient that decreases with the number of side chain cations, the wet film thickness is linked with the target dry film thickness, the solid content of the casting solution, and the side chain structure, so that the drying endpoint falls precisely in the reversible swelling window near the polymer Tg; combined with the three-stage drying process that dynamically adjusts the hot air temperature based on the membrane surface temperature (rather than the oven set temperature) as feedback, and ensuring that the membrane surface temperature does not exceed the thermal degradation temperature of the quaternary ammonium cations throughout the process, the cation clusters of the multi-quaternary ammonium flexible side chains are orderly aggregated before glass transition to form continuous ion conduction channels, while protecting the multi-quaternary ammonium side chains from degradation due to high temperature. Attached Figure Description

[0015] Figure 1 This is a synthetic route diagram of the polymer precursor and quaternized polymer of the present invention; Figure 2 The above are the 1H NMR spectra of the polymer precursor and three AEMs of the present invention. Figure 3 This is a comparison chart of the mechanical properties (stress-strain curves) of three membranes according to embodiments of the present invention; Figure 4 The following are the OH- ion conductivity curves of three membranes as a function of temperature in embodiments of the present invention; Figure 5 The Arrhenius fitting curves for the OH- ion conductivity of three membranes in the embodiments of the present invention are shown below. Figure 6 The conductivity retention curves of three membranes in embodiments of the present invention after immersion in 1 M KOH at 80°C for 1000 h are shown. Figure 7 The polarization curves of the AEMWE single cell based on the three films of the present invention at 60°C are shown. Detailed Implementation

[0016] The embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and should not be construed as limiting the scope of the invention.

[0017] This invention provides a technical solution: a multi-quaternary ammonium anion exchange membrane containing pyridine cations, comprising the following general structural formula: Where n is the degree of polymerization, Ar is the aromatic hydrocarbon residue, NR represents the flexible side chain R grafted onto the nitrogen atom of the pyridine ring, and OH - For ions; In the above general formula, the R structure can be any of the following: Monoquaternary ammonium cationic side chain: —(CH2)6—N + (CH3)3; Biquaternary ammonium cationic side chain: —(CH2)4—N + (CH3)2—(CH2)6—N + (CH3)3; The triquaternary ammonium cationic side chain is derived from the Br-DQA bisquaternary ammonium salt, the structure of which is [Br - [(CH3)3N] + —(CH2)6—N + [(CH3)2—(CH2)4—Br], with the ion being Br. - The general structural formula is as follows: The Ar structure can be any of the following: p-terphenyl residue, biphenyl residue; the general structural formula is as follows: The preparation steps are as follows: S1. Synthesis of precursor polymer: Using aromatic hydrocarbons and 4-acetylpyridine as monomers, dichloromethane as solvent, and trifluoromethanesulfonic acid as catalyst, polyarylpyridine precursors are synthesized via superacid-catalyzed Friedel-Crafts hydroxyalkylation reaction. The molar ratio of the aromatic hydrocarbon to 4-acetylpyridine and trifluoromethanesulfonic acid is 1:1 to 2:5 to 10, the reaction temperature is 0°C to room temperature, and the reaction time is 12 to 24 hours. S2. Preparation of quaternized polymer: The precursor polymer obtained in step S2 is dissolved in a polar solvent, and an alkali and a quaternizing agent are added successively. The reaction is carried out at 60-80℃ for 48-120 hours. After precipitation, washing and drying, the quaternized polymer is obtained. The quaternizing agent is selected from iodomethane, 1-bromo-6-trimethylammonium hexyl bromide or Br-DQA bisquaternary ammonium salt, and is used to prepare monocationic, dicationic and tricationic side chain polymers, respectively. S3. Preparation of anion exchange membrane: Dissolve the quaternized polymer obtained in step S2 in a polar solvent to prepare a homogeneous casting solution with a polymer mass fraction of 5-15 wt%. After filtration and degassing through a glass frit funnel (G2), the solution is uniformly cast onto a clean horizontal glass plate or flat plate to form a wet membrane. The thickness of the wet membrane is set by adjusting the gap between the doctor blade and the die lip. h_wet = h_dry × (1 + k / w) Where h_dry is the target dry film thickness of 30~80μm, w is the polymer mass fraction of the casting solution, and k is the solid content correction coefficient, with a value range of 0.85~1.15, which decreases with the increase of the number of quaternary ammonium cations in the flexible side chain. The glass substrate with the film was then placed in a segmented temperature-controlled oven for three-stage controlled drying with film surface temperature feedback. The first stage involves drying at a membrane surface temperature of 30-50℃ for 0.5-2 hours to establish a solvent evaporation gradient and induce the initial aggregation of side-chain cation clusters. The second stage involves drying the film surface at a temperature of 50-70℃ for 2-6 hours to reduce the solvent residue to below 2wt% and allow the cationic clusters of the multi-quaternary ammonium flexible side chains to aggregate in an orderly manner within the reversible swelling window near the polymer's glass transition temperature Tg, forming a continuous ion conduction channel. The third stage involves drying at a film surface temperature of 70~90℃ and not exceeding 110℃ for 0.5~2 hours to eliminate residual stress and reduce solvent residue to below 0.5wt%. The oven hot air temperature is dynamically adjusted based on the real-time monitoring of the film surface temperature by a non-contact temperature sensor closely attached to the film surface. The film surface temperature does not exceed 110℃ throughout the drying process to protect the quaternary ammonium cation groups from degradation due to high temperatures. The quaternized polymer has an ether-free polyarylpyridine backbone, and flexible side chains containing 1-3 quaternary ammonium cation groups are grafted onto its pyridine nitrogen atoms. The resulting film is immersed in a 1 M KOH or NaOH solution and subjected to alkali exchange at 60-80℃ for 12-24 hours to obtain OH... - Anion exchange membrane in the form of anion exchange membrane.

[0018] In step S2, the Br-DQA bisquaternary ammonium salt is synthesized in two steps: first, iodomethane is reacted with N,N,N',N'-tetramethyl-1,6-hexanediamine to generate a monoquaternized intermediate, and then the intermediate is reacted with 1,4-dibromobutane to generate Br-DQA.

[0019] The polar solvent is dimethyl sulfoxide; the base is anhydrous potassium carbonate.

[0020] It also includes the following embodiments (such as) Figures 1-7 (as shown) Example 1: Synthesis of precursor polymers In a 100 mL dry three-necked round-bottom flask, terphenyl (3.59 g, 15.61 mmol) and 4-acetylpyridine (2.47 g, 20.37 mmol) were added sequentially, followed by 10 mL of anhydrous dichloromethane. The mixture was magnetically stirred under nitrogen protection until the monomers were completely dissolved. The flask was placed in an ice bath at 0°C, and trifluoromethanesulfonic acid (16.4 mL) was slowly added dropwise through a constant-pressure dropping funnel at a rate of 1 mL / min. After the addition was complete, the ice bath was removed, and the reaction system was allowed to warm naturally to room temperature. The reaction was continued with stirring for 12 hours. After the reaction was complete, the viscous reaction solution was slowly poured into 500 mL of vigorously stirred ethyl acetate, resulting in the precipitation of a pale yellow fibrous polymer. The precipitate was collected by filtration, washed three times with tap water and three times with anhydrous ethanol, and dried in a vacuum oven at 80°C for 24 hours to obtain a pale red PTAP precursor powder.

[0021] Example 2: Synthesis of Br-DQA bisquaternary ammonium salt 117.90 mmol of iodomethane was dissolved in 50 mL of ethyl acetate and slowly added dropwise to a mixed solution containing 233.88 mmol of N,N,N',N'-tetramethyl-1,6-hexanediamine and 300 mL of ethyl acetate under magnetic stirring. The reaction was carried out at room temperature in the dark for 24 hours with stirring. After the reaction was completed, the white precipitate was collected by filtration, washed three times each with n-hexane and ethyl acetate, and dried under vacuum to obtain the DQA intermediate.

[0022] 10.19 mmol of the DQA intermediate was dissolved in 43 mL of anhydrous acetonitrile and slowly added dropwise at room temperature to a mixed solution containing 111.81 mmol of 1,4-dibromobutane and 43 mL of acetonitrile. The reaction was continued with stirring for 24 hours. After the reaction was completed, insoluble byproducts were removed by filtration. The filtrate was concentrated under reduced pressure, and tetrahydrofuran was added to precipitate a white solid. The solid was filtered, washed three times with tetrahydrofuran, and dried under vacuum to obtain the Br-DQA monomer.

[0023] Example 3: Synthesis of a single cationic polymer Weigh 1.50 g of the polymer precursor and place it in a 250 mL dry single-necked round-bottom flask. Add 20 mL of anhydrous DMSO and stir at 40 °C until completely dissolved. Add anhydrous K₂CO₃ (1.5 equivalents relative to the nitrogen atom of the pyridine ring), stir thoroughly, and then add 5 equivalents of iodomethane. Seal the flask, protect from light, and stir at 80 °C for 96 hours. After the reaction is complete, slowly pour the reaction solution into 500 mL of ethyl acetate to precipitate the product. Filter and collect the precipitate, wash three times each with anhydrous ethanol and deionized water, and dry under vacuum at 60 °C for 24 hours to obtain the monocationic polymer (PTAP-Me) in 92.5% yield.

[0024] Example 4: Synthesis of a dicationic polymer Weigh 1.50 g of the PTAP precursor polymer and place it in a 250 mL three-necked round-bottom flask. Add 20 mL of anhydrous DMSO and stir at 60 °C until completely dissolved. Add 2.5 equivalents of anhydrous K₂CO₃ and stir thoroughly. Dissolve 2 equivalents of 1-bromo-6-trimethylammonium hexyl bromide in a mixed solution of 16 mL NMP and 18 mL DMSO, and slowly add the solution dropwise to the flask. Stir the reaction mixture at 60 °C under nitrogen protection for 96 h. After the reaction is complete, pour the reaction solution into 500 mL of ethyl acetate to precipitate the polymer. Filter the precipitate, wash and dry to obtain the dicationic polymer (PTAP-C6) with a yield of 82.8%.

[0025] Example 5: Synthesis of Tricationic Polymers The synthesis procedure was the same as in Example 4, except that 1-bromo-6-trimethylammonium hexyl bromide was replaced with an equivalent amount of Br-DQA obtained in Example 2. After the reaction was completed, the tricationic polymer (PTAP-DQA) was obtained after precipitation, washing, and drying, with a yield of 70.4%.

[0026] Example 6: Preparation of anion exchange membrane 0.8 g of each of the PTAP-Me, PTAP-C6, and PTAP-DQA polymers were weighed and dissolved in 7.2 g of DMSO. The solutions were stirred at room temperature for 12 hours to form a homogeneous solution. After filtration through a G2 glass frit funnel, the solution was uniformly cast onto a clean horizontal glass plate and dried in a 70°C oven for 12 hours to form a uniform film with a thickness of approximately 50 µm. The film was then allowed to peel off naturally by immersion in deionized water. The films were then immersed in a 1 M KOH solution at 60°C for 12 hours for anion exchange, repeatedly rinsed with deionized water until neutral, and stored in nitrogen-filled deionized water. These films were designated as PTAP-Me, PTAP-C6, and PTAP-DQA membranes, respectively.

[0027] Example 7: AEMWE Single Cell Test A membrane electrode was prepared using a catalyst coating substrate method, with an effective area of ​​4 cm². The cathode Pt catalyst loading was 0.5 mg·cm². 2 The PTAP-DQA polymer (5 wt% DMSO solution) of this invention was used as the ionomer. The anode used a NiFe-based self-supporting nickel foam catalyst with a loading of approximately 3.5 mg·cm³. 2 The membrane electrode was tested at 60°C in 1 M KOH electrolyte. The results showed that the AEMWE based on the PTAP-DQA membrane achieved a current density of 2.9 A·cm⁻¹ at 2.0 V. 2 .

[0028] Example 8: Three-stage controlled drying film formation using Tg-anchor point critical thickness control and film surface temperature feedback 0.8g of PTAP-DQA polymer (triquaternary ammonium side chain, k≈0.90) was dissolved in 7.2g of DMSO and stirred at room temperature for 12 hours to form a homogeneous casting solution (approximately 10wt%, w=0.10). The adjustable doctor blade gap was set to 500μm according to h_wet=h_dry×(1+k / w)=50μm×(1+0.90 / 0.10)=500μm. The casting solution was then uniformly poured onto a clean, horizontal glass plate. The glass plate was placed in a segmented temperature-controlled oven. An infrared temperature sensor attached to the film surface was used to monitor the film surface temperature T_s in real time and dynamically adjust the hot air temperature accordingly: the first segment had a T_s of 40℃ for 1 hour (T_oven≈50℃), establishing a volatile gradient and allowing the PTAP-DQA side chain cationic clusters to initially aggregate. In the second stage, T_s is 60℃ for 4h (T_oven≈70℃), the solvent residue is reduced to <2wt%, and the multi-quaternary ammonium flexible side chain cationic clusters are orderly aggregated in the reversible swelling window near the polymer Tg, forming a continuous ion conduction channel; The third stage has a T_s of 85℃ (≤110℃) and a T_oven of 1h (T_oven≈95℃), which eliminates residual stress and reduces solvent residue to <0.5wt%.

[0029] The membrane surface temperature T_s ≤ 110℃ throughout the process to protect the triquaternary ammonium side chains from degradation due to high temperature. Drying to constant weight yields a dense, non-porous PTAP-DQA precursor membrane with a thickness of approximately 50 μm. Finally, it undergoes alkali exchange in 1 M KOH at 60℃ for 12 h, followed by washing with deionized water until neutral, to obtain OH... - Type membrane.

[0030] Testing showed that the PTAP-DQA membrane prepared using the process of Example 8 of this invention, while maintaining its dense and non-porous structure (meeting the gas barrier requirements of AEMWE membranes), exhibited good performance at 80°C OH. - The conductivity reaches 153 mS / cm, and the A·cm at 2.0V reaches 2.9A. - ², and due to the protective constraint of a membrane surface temperature ≤110℃ throughout the process, the multi-quaternary ammonium side chains did not undergo significant thermal degradation.

[0031] In summary, this pyridine-cation-containing multi-quaternary ammonium anion exchange membrane and its preparation method, using ether-free polyarylpyridine as the backbone, fundamentally avoids the risk of ether degradation under alkaline conditions, endowing the membrane material with excellent alkali resistance and stability. Simultaneously, by grafting flexible side chains containing one to three quaternary ammonium cations onto the pyridine nitrogen atom via the Menshutkin reaction, precise control of the number of side chain cations is achieved. The multi-cation structure and long flexible side chains synergistically construct a continuous and efficient ion transport channel, and the electrostatic repulsion between cations effectively inhibits excessive extension of the polymer chain. This achieves a good balance between improved ion conductivity and low swelling rate, resulting in anion exchange membranes that possess high conductivity, excellent dimensional stability, and alkali resistance, meeting the application requirements of anion exchange membranes in water electrolysis for hydrogen production.

[0032] In the film-forming drying process, a three-stage controlled drying method with Tg-anchor critical thickness control and film surface temperature feedback is introduced: By using the glass transition temperature as the anchor point and combining a solid content correction coefficient that decreases with the number of side chain cations, the wet film thickness is linked with the target dry film thickness, the solid content of the casting solution, and the side chain structure, so that the drying endpoint falls exactly in the reversible swelling window near the polymer Tg; combined with the three-stage drying method that dynamically adjusts the hot air temperature with film surface temperature (rather than the oven set temperature) as feedback, and ensures that the film surface temperature does not exceed the thermal degradation temperature of quaternary ammonium cations throughout the process, the cation clusters of multiple quaternary ammonium flexible side chains are promoted to aggregate in an orderly manner before glass transition, forming continuous ion conduction channels, while protecting the multiple quaternary ammonium side chains from degradation due to high temperature.

[0033] The embodiments of the present invention are given for illustrative and descriptive purposes only, and are not intended to be exhaustive or to limit the invention to the forms disclosed. Many modifications and variations will be apparent to those skilled in the art. The embodiments were chosen and described in order to better illustrate the principles and practical application of the invention, and to enable those skilled in the art to understand the invention and to design various embodiments with various modifications suitable for a particular purpose.

Claims

1. A multi-quaternary ammonium anion exchange membrane containing pyridine cations, characterized in that: Including the following general structural formulas: Where n is the degree of polymerization, Ar is the aromatic hydrocarbon residue, NR represents the flexible side chain R grafted onto the nitrogen atom of the pyridine ring, and OH - It is a para ion.

2. The multi-quaternary ammonium anion exchange membrane containing pyridine cations according to claim 1, characterized in that: In the general formula, the R structure can be any of the following: Monoquaternary ammonium cationic side chain: —(CH2)6—N + (CH3)3; Biquaternary ammonium cationic side chain: —(CH2)4—N + (CH3)2—(CH2)6—N + (CH3)3; The triquaternary ammonium cationic side chain is derived from the Br-DQA bisquaternary ammonium salt, the structure of which is [Br - [(CH3)3N] + —(CH2)6—N + [(CH3)2—(CH2)4—Br], with the ion being Br. - The general structural formula is as follows: 。 3. The multi-quaternary ammonium anion exchange membrane containing pyridine cations according to claim 1, characterized in that: In the general structural formula, the Ar structure is any one of the following: a terphenyl residue or a biphenyl residue; the general structural formula is as follows: 。 4. A method for preparing a multi-quaternary ammonium anion exchange membrane containing pyridine cations, used to prepare the multi-quaternary ammonium anion exchange membrane containing pyridine cations as described in any one of claims 1-3, characterized in that: Includes the following steps: S1. Synthesis of precursor polymer: Using aromatic hydrocarbons and 4-acetylpyridine as monomers, dichloromethane as solvent, and trifluoromethanesulfonic acid as catalyst, polyarylpyridine precursors are synthesized via superacid-catalyzed Friedel-Crafts hydroxyalkylation reaction. The molar ratio of the aromatic hydrocarbon to 4-acetylpyridine and trifluoromethanesulfonic acid is 1:1 to 2:5 to 10, the reaction temperature is 0°C to room temperature, and the reaction time is 12 to 24 hours. S2. Preparation of quaternized polymer: The precursor polymer obtained in step S2 is dissolved in a polar solvent, and an alkali and a quaternizing agent are added successively. The reaction is carried out at 60-80℃ for 48-120 hours. After precipitation, washing and drying, the quaternized polymer is obtained. The quaternizing agent is selected from iodomethane, 1-bromo-6-trimethylammonium hexyl bromide or Br-DQA bisquaternary ammonium salt, and is used to prepare monocationic, dicationic and tricationic side chain polymers, respectively. S3. Preparation of anion exchange membrane: Dissolve the quaternized polymer obtained in step S2 in a polar solvent to prepare a homogeneous casting solution with a polymer mass fraction of 5-15 wt%. After filtration and degassing through a glass frit funnel (G2), the solution is uniformly cast onto a clean horizontal glass plate or flat plate to form a wet membrane. The thickness of the wet membrane is set by adjusting the gap between the doctor blade and the die lip. h_wet = h_dry × (1 + k / w) Where h_dry is the target dry film thickness of 30~80μm, w is the polymer mass fraction of the casting solution, and k is the solid content correction coefficient, with a value range of 0.85~1.15, which decreases with the increase of the number of quaternary ammonium cations in the flexible side chain. The glass plate with the film was then placed in a segmented temperature-controlled oven for three-stage controlled drying with film surface temperature feedback to obtain OH. - Anion exchange membrane in the form of anion exchange membrane.

5. The method for preparing a multi-quaternary ammonium anion exchange membrane containing pyridine cations according to claim 4, characterized in that: In step S2, the Br-DQA bisquaternary ammonium salt is synthesized in two steps: first, iodomethane is reacted with N,N,N',N'-tetramethyl-1,6-hexanediamine to generate a monoquaternized intermediate, and then the intermediate is reacted with 1,4-dibromobutane to generate Br-DQA.

6. The method for preparing a multi-quaternary ammonium anion exchange membrane containing pyridine cations according to claim 4, characterized in that: The polar solvent is dimethyl sulfoxide; the base is anhydrous potassium carbonate.

7. The method for preparing a multi-quaternary ammonium anion exchange membrane containing pyridine cations according to claim 4, characterized in that: In step S3, the value of k is: k≈1.0 for monoquaternary ammonium side chain, k≈0.95 for diquaternary ammonium side chain, and k≈0.90 for triquaternary ammonium side chain.

8. The method for preparing a multi-quaternary ammonium anion exchange membrane containing pyridine cations according to claim 4, characterized in that: In step S3, the three-stage controlled drying with membrane surface temperature feedback is as follows: The first stage involves drying at a membrane surface temperature of 30-50℃ for 0.5-2 hours to establish a solvent evaporation gradient and induce the initial aggregation of side-chain cation clusters. The second stage involves drying the film surface at a temperature of 50-70℃ for 2-6 hours to reduce the solvent residue to below 2wt% and allow the cationic clusters of the multi-quaternary ammonium flexible side chains to aggregate in an orderly manner within the reversible swelling window near the polymer's glass transition temperature Tg, forming a continuous ion conduction channel. The third stage involves drying at a film surface temperature of 70~90℃ and not exceeding 110℃ for 0.5~2 hours to eliminate residual stress and reduce solvent residue to below 0.5wt%. The oven hot air temperature is dynamically adjusted based on the real-time monitoring of the film surface temperature by a non-contact temperature sensor closely attached to the film surface. The film surface temperature does not exceed 110℃ throughout the drying process to protect the quaternary ammonium cation groups from degradation due to high temperatures. The quaternized polymer has an ether-free polyarylpyridine backbone, and flexible side chains containing 1-3 quaternary ammonium cation groups are grafted onto its pyridine nitrogen atoms. The resulting film is immersed in a 1 M KOH or NaOH solution and subjected to alkali exchange at 60-80℃ for 12-24 hours to obtain OH... - Anion exchange membrane in the form of anion exchange membrane.